Analysis of Intersectional Feminism in the Short Story "Hijab, My Crown" - Fadhila Nur Jayanti; Yulia Nurhalimah; Lauvia Shabrinnah (Morphosis: Journal of Literature, 2024)
The short story is one of the most interesting works of literature to analyze. the short story contains issues that describe the phenomenon of an environment what happens in everyday life and how the government responds to its people. The short story "Hijab, My Crown" presents a gender issue that focuses on intersectional feminism, the intersectional theory was proposed by Kimberle Crenshaw. the theory gives an understanding of how hijab can be a symbol of freedom and empowerment for Muslim women who make them feel safe and comfortable when using hijab, but on the other hand, hijab can also be a symbol of oppression for Muslim women who feel forced to use hijab. with qualitative research methods and data collection through content analysis in short stories, the results show that women who wear hijab often get discriminated against in the surrounding environment and it makes them feel uncomfortable, freedom and religious beliefs become restrictions for themselves. Keywords: intersectional feminism; hijab; women oppression; discriminated